Cultural Melancholy : Readings of Race, Impossible Mourning, and African American Ritual - Singleton, Jermaine, 1974- (Book collections on Project MUSE., 2015)
"More than 130 years have passed since the ratification of the 13th Amendment and the U.S. Constitution declared slavery illegal, yet the nation still suffers from legacies of slavery. In this cultural and literary studies project, Singleton charts new territory in the relationship between critical race studies, psychoanalysis and performance studies to explore and address the psychic and social remains of the nation's history of slavery and discrimination in a post-racial moment. The book brings psychoanalytic paradigms of mourning and melancholia and discussions of race and performance into conversation with literary representations of America's post-Emancipation life and ritual practice to challenge scholarship that fails to engage with both ethnic studies and psychoanalysis to interpret history. The work further explores how theatrical and musical performance contribute to the construction and deconstruction of historical and subjective grief over U.S. racial legacies. Singleton develops a theory of cultural melancholy to provide a framework to engage a process that, through which modern ritual practices, constructs, maintains, and link normative and minority racial positions in relation to social loss and unresolved grief. The discussion of primary texts ranges from F. Scott Fitzgerald's The Great Gatsby to James Baldwin's Go Tell It on the Mountain to Billie Holiday's memoir, and in the process ranges different geographical, political, and historical senses. By analyzing African American and white subject-formations as represented in literature, drama, and musical performance in the twentieth century, the project helps us understand the process of coming to terms with historical traumas of slavery, segregation, and racial discrimination"--